The Effect Of Content Development On Android Applications On Knowledge Of Dietary Prescriptions On Metabolic Syndrome Risk - Tetes Wahyu W; Rinda Nur Hidayati; Jumiyati Jumiyati; Atika Hendryani (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2022)
Metabolic syndrome is generally defined as meeting 3 (three) of 5 (five) criteria including abdominal obesity, hypertriglyceridemia, low HDL (high density lipoprotein) cholesterol, hypertension and hyperglycemia. About 20-25% of the world's adult population has the metabolic syndrome. The purpose of this study was to determine the effect of the android application on knowledge of dietary prescriptions in the community at risk for metabolic syndrome. The research design is a quasi-experimental study (quasi-experimental study), with a non-randomized control group pre-test - post-test test design that aims to determine the possibility of a causal relationship by intervening or giving treatment to one or more experimental groups, then the results (effect) of intervention was compared with a group that was subjected to different treatments (control group). Characteristics of age (p=0.172), gender (p=0.25) and education (p=0.055). Knowledge before intervention p=0,306 and after intervention p=0,009 in both groups. Knowledge before and after intervention in the case group p=0.0005 and knowledge before and after intervention in the control group p=0.0005. The types of outputs produced in this study are application systems for early detection of metabolic syndrome disease and dietary prescriptions, intellectual property rights and research journal articles. Introducing this android application so that it can be better known to the public in general and developing this android application so that it becomes more interesting and easy to understand.